The role of wind in the near field and midfield of a river plume. Issue 14 (30th July 2014) - Kakoulaki, Georgia; MacDonald, Daniel; Horner‐Devine, Alexander R.
Abstract The role of wind in the near‐field and midfield regions of the Merrimack River plume is quantified using observations from surface drifters released near the river mouth during ebb tide in 2009, 2010, and 2011 under a range of wind and river discharge conditions. Comparison of momentum balance terms and analysis of plume trajectories suggests that the plume is sensitive to wind direction for wind speeds >4 m s−1 in all regions of the plume, including the near field, where wind influence has typically been considered second order. Intermediate ranges (4–12 km) were more strongly influenced by the wind than the near field (0–4 km). However, the influence of the instantaneous wind diminished farther from the mouth, presumably, due to the growing importance of longer time scale process (i.e., Ekman transport). The plume was less sensitive to cross‐shore winds than alongshore winds, particularly near the river mouth, where momentum dominates.